The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s1517-83822014000400019
|View full text |Cite
|
Sign up to set email alerts
|

Gram-negative intestinal indigenous microbiota from two Siluriform fishes in a tropical reservoir

Abstract: The Gram-negative intestinal microbiota of Hypostomus auroguttatus and Pimelodus maculatus, a detritivorous and an omnivorous fish species, respectively, were compared between fishes from the reservoir and the stretch of the river below the dam of the Funil hydroelectric plant, Rio de Janeiro, Brazil. Four selective culture media were used under aerobic and two under anaerobic conditions. The omnivorous species had microbiota with higher population levels compared to the detritivorous species. The number of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…This group has been recognised to produce butyric acid as a major product of fermentation [ 85 ], and some species have been associated with diseases in mammals [ 86 ]. Fusobacteria are the most abundant phylum of the autochthonous normal gut microbiota in common carp [ 37 ], and are also well represented in the gut microbiota of some lab reared zebrafish [ 78 ] and tropical siluriform fish [ 87 ]. Other authors have reported the presence of Fusobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…This group has been recognised to produce butyric acid as a major product of fermentation [ 85 ], and some species have been associated with diseases in mammals [ 86 ]. Fusobacteria are the most abundant phylum of the autochthonous normal gut microbiota in common carp [ 37 ], and are also well represented in the gut microbiota of some lab reared zebrafish [ 78 ] and tropical siluriform fish [ 87 ]. Other authors have reported the presence of Fusobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to those fish cited in a previous review (28), recent investigations have isolated Plesiomonas from rainbow trout (53,54), carp (55), and tilapia (44,56,57). Studies of the intestinal tracts of a number of freshwater fish suggest that the genus Plesiomonas is one of the most common species composing the bacterial microbiota of these vertebrates, in addition to Fusobacterium and Aeromonas (58,59). An Auburn University study pooled DNA samples from the intestinal contents of three commercial freshwater species and subjected these samples to 16S rRNA gene pyrosequencing (58).…”
Section: Invertebrate and Vertebrate Hostsmentioning
confidence: 99%
“…Changing the diet of puffer fish from the natural habitat to non-typical food led to a loss of animal toxicity, and returning to a natural diet restored toxicity [ 101 ]. As shown for many animals, including fish, a diet change to non-typical food causes changes in the qualitative and quantitative composition of intestinal microflora [ 105 , 106 ]. Diet normalization causes recovery of intestinal microflora [ 107 ].…”
Section: Discussionmentioning
confidence: 99%